Reducing the cost of biodiesel production with support of its by products - Chavan S.B.; Sharma Y.C. (My University, 2025)
Self-reliance in energy is vital for overall economic development of our country. Biodiesel has attracted considerable attention during the past decade as a renewable, biodegradable and nontoxic fuel. Ttransesterification using alkali as a catalyst is a popular method for biodiesel production. Study explores wastes or byproducts seed cover, de-oiled cake, water wash analysis and its utility for growth of biodiesel industry in future. Study concludes that, it may reduce the cost of biodiesel production and can support biodiesel to commercialize in the form of blending. The reported work is unique, important and interesting. © 2018 Scientific Publishers. All rights reserved.